1999
DOI: 10.1046/j.1365-2958.1999.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

The replication checkpoint control in Bacillus subtilis: identification of a novel RTP‐binding sequence essential for the replication fork arrest after induction of the stringent response

Abstract: SummaryWe have shown previously that induction of the stringent response in Bacillus subtilis resulted in the arrest of chromosomal replication between 100 and 200 kb either side of oriC at distinct stop sites, designated LSTer and RSTer, left and right stringent terminators respectively. This replication checkpoint was also shown to involve the RTP protein, normally active at the chromosomal terminus. In this study, we show that the replication block is absolutely dependent upon RelA, correlated with high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 58 publications
3
31
0
1
Order By: Relevance
“…We have also examined the replication intermediates from the same plasmid containing the L1 core sequence by onedimensional gels and found no evidence of replication arrest, consistent with earlier published results (Ref. 8 and data not shown).…”
Section: Figsupporting
confidence: 91%
See 2 more Smart Citations
“…We have also examined the replication intermediates from the same plasmid containing the L1 core sequence by onedimensional gels and found no evidence of replication arrest, consistent with earlier published results (Ref. 8 and data not shown).…”
Section: Figsupporting
confidence: 91%
“…Perhaps the explanation for the difference is that only the 17-bp core sequence of L1 was used by them for RTP binding experiments and the binding behavior of the complete core and auxiliary sequence was not examined (8). It is, however, more difficult to explain as to why stringent response-dependent conditional arrest of replication was observed by the other group in a genomic DNA fragment that included L1 (8). We saw no evidence that replication arrest at L1 was modulated by stringent response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon was called "replication checkpoint of B. subtilis," and its functioning was shown to depend on the presence of RTP (156); however, the mechanism of regulation of the replication arrest is not known. The RTP binding site was located around one of the two arrest sites (4). It was further shown that this site was bipartite, like Ter, and bound two RTP dimers (although much more weakly than Ter sites from the terminus).…”
Section: Dna Binding Proteinsmentioning
confidence: 96%
“…The replication arrest experiments took advantage of elegant work characterizing the effects of amino acid starvation on DNA replication. On amino acid starvation (induction of the stringent response), a reversible DNA replication arrest occurs in B. subtilis in regions ∼100-130 kbp to the left (LSTer, left stringent terminus region) and ∼150-200 kbp to the right (RSTer) of the origin of replication (Levine et al 1991(Levine et al , 1995Autret et al 1999). Replication resumes in the STer regions when amino acids are added back to the cells.…”
Section: A Central Replication Factorymentioning
confidence: 99%